2008
DOI: 10.1007/bf03179448
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of modified atmosphere onSalmonella typhimurium in packaged meat during storage in the refrigerator and at 12°C

Abstract: Summary -The effects of storage atmosphere and temperatures on Salmonella typhimurium and aerobic plate count (APC) in meat were studied. Experimental results were analysed by non-linear regression of modified-Gompertz and logistic equations to generate "best fit". In the absence of CO 2 in package (with air and 40% O 2 + 60% N 2 ), in the refrigerator and at 12 o C, S. typhimurium had higher growth rate and reached to higher number, whereas the presence of CO 2 from 40 to 100% reduced the number of S. typhimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A total of 155 duplicate articles were found. After initial title, abstract, and full article reading, 83 studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 155 duplicate articles were found. After initial title, abstract, and full article reading, 83 studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ,…”
Section: Resultsmentioning
confidence: 99%
“…One study, for example, observed a reduction between 1.4 and 1.9 log CFU g −1 in Salmonella concentrations in ground beef packed under a vacuum and in a modified atmosphere at 3 °C for 12 days [ 17 ]. In another study, 0.17 and 0.97 log CFU Salmonella -concentration decreases were detected in modified-atmosphere packed (MAP) beef stored at 7.5 °C for 12 days, although a 1.69 log CFU g −1 pathogen reduction was observed in vacuum-packed beef in the same study [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two gases, CO 2 and N 2 are commonly used in MAP, the first being mainly responsible for the bacteriostatic or bactericidal effect on microorganisms. For meat and meat products, red color maintenance is important (Erkmen and Barazi, 2008;Erkmen and Bozoglu, 2008a). During storage of E. coli O157:H7 inoculated sliced meat at 4°C in 30% CO 2 atmosphere, the pathogen showed significant (p0.05) reduction compared to similar conditions in air.…”
Section: Discussionmentioning
confidence: 99%
“…Fax: +90 3423601011. product storage (Erkmen and Bozoglu, 2008a). Pathogen behavior on raw meats, as with many other foods, is controlled by several interrelated factors, such as temperature of storage, atmosphere composition and competitive microflora (ICMSF, 1998;Erkmen and Barazi, 2008;Erkmen and Bozoglu, 2008a). The current assumption is that E. coli O157:H7 does not multiply below 7°C, which is the endpoint generally accepted by the European Union as an appropriate temperature to prevent mesophilic pathogen growth (Anon, 2004).…”
Section: Introductionmentioning
confidence: 99%